Implementasi Coretax terhadap Efisiensi Proses Administrasi Perpajakan dan Kepuasan Wajib Pajak di Era Digital: (Studi Kasus Di KPP Pratama Kediri) - Abrilla Hani Artavia; Miladiah Kusumaningarti; Puji Rahayu (Owner : Riset dan Jurnal Akuntansi, 2026)
Starting in 2025, the integrated tax administration system (also known as Coretax) will be implemented in Indonesia with the aim of increasing the effectiveness and transparency of the country's tax administration system. The purpose of this study is to examine the effect of administrative process efficiency (y1) on taxpayer satisfaction (y2) after the implementation of Coretax (x). The method used is purposive sampling, with data collection techniques including observation, interviews, and documentation. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the large variable of administrative process efficiency (Y1) has a more dominant effect on the level of taxpayer satisfaction (Y2) after the implementation of Coretax (X), that the administrative process efficiency (Y1) has a more dominant effect. The implications of this study are to encourage taxpayer digital literacy so that services become faster and more effective.